Perbandingan Upah Anggota dan Bukan Anggota Serikat Pekerja di Indonesia: Dekomposisi Blinder-Oaxaca - Nugraha, Hafiyyanti; Handayani, Dwini (Jurnal Manajemen Bisnis dan Keuangan, 2022)
This study aims to study the differences in wages for members and non-union members in Indonesia with a sample of 17,650 data. The details of the sample used are 1,855 samples are workers union members, and 15,795 samples are non-union members aged 15-64 years from IFLS5 2014, both formal and informal workers. The results of the Blinder-Oaxaca decomposition of the difference between the wages of members and non-union members show that union members earn 0.40 log points higher wages than workers who are not union members. Meanwhile, in the formal sector, the wage difference was higher, reaching 0.50 log points. The gap that occurs is explained by two main factors, namely the explained factor or worker characteristics factor and the unexplained factor. Unexplained factors are other factors that are not included in the research model, such as employment positions and company characteristics. The contribution of the explained factor to all workers contributed the most to the wage gap. In general, workers who are members of trade unions are concentrated in the male gender, have higher education, and live in urban areas.